How Artificial Intelligence Changes the Role of Lawyers in the Provision of Legal Services - Sabirovna, Yunusova Minavvarkhon (International Journal of Psychosocial Rehabilitation, 2020)
For the first time, five areas of legal activity are formulated in the paper, which will significantly change under the influence of artificial intelligence in the near future: (1) information search on the circumstances of the case; (2) search for precedents; (3) preparation of documents; (4) preparing the case file; and (5) predicting the outcome of the case. In addition, even now, computer technology is in significant competition with lawyers and undermines their monopoly. Large financial companies provide computer legal services, despite the fact that while economically significant developments exist in only three of the five above-mentioned areas. The three most profitable areas in this regard are the search for precedents, the search for information on the circumstances of the case and the preparation of documents.